Qualitative diagnosis of human movement Improving performance in sport and exercise - Knudson, Duane V. (Human Kinetics, 2013)
For sport science professionals, qualitative movement diagnosis (QMD) is a critical skill in helping individuals improve performance or reduce injury risk. This edition focuses on the processes behind movement observation, assessment and diagnosis, emphasising how to recognise and correct errors in human movement.